Ternary Surface Complexes 1. Complex Formation in the System Silica-Cu(II)-Ethylenediamine - Alain C.M. Bourg; Paul W. Schindler (CHIMIA)
Studies on the adsorption of Cu(II) from aqueous solutions containing ethylenediamine (en) at the silica-water interface reveal the formation of the ternary surface complexes (⪫Si—O)Cu(en)+ (I) and (⪫Si—O)2Cu(en)0 (II). Compairing the experimentally obtained stability constants with statistical predictions indicates that the formation of (I) is slightly favored whereas the formation of (II) is slightly hindered.